PENYELESAIAN GUGATAN WANPRESTASI DALAM EKONOMI SYARIAH DI PENGADILAN AGAMA BANTUL (Analisis Putusan Perkara No. 0318/Pdt.G/2011/PA.Btl) - , MEYLLA QURRATA AINY, Prof., Dr., Abdul Ghofur Anshori, S.H., M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to find out the completion of default accusation in Islamic echonomy at Bantul Religious Court with case registration No. 0318/Pdt.G/2011/PA.Btl along with the execution of the decision. This research is a normative law, which is done by using data resources acquired from literature study, the legal research is done by researching library materials or secondary.In library research, the data was collected by reading and studying the literature regarding legal dispute resolution Islamic economics, law, copies of Bantul Religious Court Decision Number: 0318/Pdt.G/2011/PA.Btl and other books related to the research material, then from all of the sources the writer chose some of legal provisions which are closely related to the problems studied. Sources of primary data obtained from the field research carried out through interviews with respondents and interviewees study, data obtained from both the research literature and field studies were analyzed using a qualitative approach that produces descriptive data. A conclusion derived from this study is that the dispute resolution of mudharabah with Register Case No. 0318/Pdt.G/2011/PA.Btl, The Panel of Judges are not necessarily passed a decision based on a formal contract established between the parties. However The Panel of Judges should delve further agreement / contract underlying the cooperation between the parties. The decision of The Panel of Judges based on the substance from the contract itself. Implementation of this decision at this case is not implemented voluntarily by parties who were sentenced for carrying out of the decision. To get justice it was carried out of execution. In the execution process, the parties agree to do the decision in a willingness so that the execution appeal has done.